Associations of loneliness with poor physical health, poor mental health and health risk behaviours among a nationally representative community‐dwelling sample of middle‐aged and older adults in India. (6th July 2021) - Pengpid, Supa; Peltzer, Karl
Abstract: Objectives: Loneliness may negatively impact on health outcomes. The study aimed to estimate the associations between loneliness and poor physical health, poor mental health, and health risk behaviours in middle‐aged and older adults in a national population survey in India. Methods: The sample included 72, 262 middle‐aged and older adults from a cross‐sectional national community‐dwelling survey in India in 2017–2018. Results: Results indicate that the prevalence of moderate loneliness was 20.5%, and severe loneliness was 13.3%. In the adjusted logistic regression analysis, moderate and/or severe loneliness was significantly positively associated with fair or poor self‐rated health status, and significantly negatively associated with life satisfaction and cognitive functioning. Furthermore, loneliness was associated with stroke, angina, physical injury, difficulty of Activities of Daily Living, difficulties of Instrumental Activities of Daily Living and multi‐morbidity. Loneliness increased the odds of major depressive disorder and insomnia symptoms. The associations between loneliness and current tobacco use and body mass index were negative and between loneliness and physical inactivity and underweight were positive. Conclusions: Loneliness is associated with poor physical health, poor mental health and health risk behaviour (physical inactivity), emphasising the need to consider loneliness in various physical and mental health contexts. Key Points: Moderate and/or severe loneliness was significantly positively associated with fair or poor self‐rated health status. Moderate and/or severe loneliness was significantly negatively associated with life satisfaction and cognitive functioning. Loneliness was associated with stroke, angina, physical injury, difficulty of Activities of Daily Living, difficulties of Instrumental Activities of Daily Living and multi‐morbidity. High odds were found between loneliness and major depressive disorder and insomnia symptoms.